2007
DOI: 10.1051/0004-6361:20066790
|View full text |Cite
|
Sign up to set email alerts
|

The superrotation of solar supergranules

Abstract: Context. Supergranules have long been believed to rotate faster than plasma and than magnetic structures. However, it has recently been shown that this could be due to a bias appearing when using Dopplergrams, which are strongly affected by projection effets. Aims. Our purpose is to perform new measurements of supergranule angular velocities using a technique that would not be significantly influenced by projection effets. Methods. We are therefore tracking horizontal divergence maps smoothed on the supergranu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
1
9
0
2
Order By: Relevance
“…The measured anisotropy of the magnetic field is but one result in a series of puzzling observations associated with supergranulation. Other observations include, for example, the finding that the supergranulation pattern rotates faster around the Sun than magnetic features (e.g., Snodgrass & Ulrich 1990;Meunier & Roudier 2007) and the wavelike properties of supergranulation (Gizon et al 2003;Schou 2003). How these phenomena are related to the discovery in this paper is unclear.…”
Section: Resultsmentioning
confidence: 84%
“…The measured anisotropy of the magnetic field is but one result in a series of puzzling observations associated with supergranulation. Other observations include, for example, the finding that the supergranulation pattern rotates faster around the Sun than magnetic features (e.g., Snodgrass & Ulrich 1990;Meunier & Roudier 2007) and the wavelike properties of supergranulation (Gizon et al 2003;Schou 2003). How these phenomena are related to the discovery in this paper is unclear.…”
Section: Resultsmentioning
confidence: 84%
“…Even more recently, Hathaway et al (2006) argued that the supergranulation pattern superrotation inferred from Doppler shifts was due to projection effects on the line-of-sight signal. Using correlation tracking of divergence maps derived from intensity maps (Meunier et al, 2007c) and comparing it with direct Doppler tracking, Meunier and Roudier (2007) confirmed the existence of projection effects with the latter method, but found that the supergranulation pattern inferred from divergence maps was still superrotating, albeit at smaller angular velocities than those inferred by Duvall Jr (1980) and Snodgrass and Ulrich (1990). For a detailed discussion on the identification of supergranulation rotational properties with helioseismology, we refer the reader to the review article by Gizon and Birch (2005) on local helioseismology.…”
Section: Rotational Properties Of Supergranulesmentioning
confidence: 72%
“…We have tracked supergranules as described in Meunier & Roudier (2007). This tracking is a combination of local correlation and feature tracking, as the local correlation is computed only at places where the divergence is maximum: we therefore track the positions of maximum divergence.…”
Section: Evolution Of the Cellsmentioning
confidence: 99%